Raster-scanned carbon ion therapy for malignant salivary gland tumors: acute toxicity and initial treatment response - Jensen, Alexandra; Nikoghosyan, Anna; Ecker, Swantje; Ellerbrock, Malte; Debus, Jürgen; Herfarth, Klaus; Münter, Marc (Radiation oncology, 2011)
To investigate toxicity and efficacy in high-risk malignant salivary gland tumors (MSGT) of the head and neck. Local control in R2-resected adenoid cystic carcinoma was already improved with a combination of IMRT and carbon ion boost at only mild side-effects, hence this treatment was also offered to patients with MSGT and microscopic residual disease (R1) or perineural spread (Pn+).